New insights into bromate removal by UV/sulfite process: Influencing factors, mechanism, and energy efficiency. (August 2022) - Yu, Yanghai; Feng, Liying; Qiao, Junlian; Guan, Xiaohong
Abstract: In recent years, the UV/sulfite process has shown high superiority in removing toxic halogenated organic compounds and oxyanions. Herein, the reduction of bromate (BrO3 ˉ) in this process was reinvestigated. The reduction of BrO3 ˉ in this process was influenced by some key coexisting species. A significant inhibition on the reduction of BrO3 ˉ was observed in the presence of dissolved oxygen (DO). Nevertheless, increasing sulfite dosage could effectively mitigate the negative impact of DO on the reduction of BrO3 ˉ. Humic acid (HA) could influence the reduction of BrO3 ˉ through the enhancement of hydrated electron (eaq ˉ) yield or the scavenging of eaq ˉ. It should be noted that the presence of Cl − and HCO3 − had an insignificant influence on the reduction of BrO3 ˉ. In this process, besides eaq ˉ, sulfite radical (SO3 − ) also contributed to the reduction of BrO3 ˉ, which was evidenced by scavenging experiments and fitting of a kinetic model. Moreover, the energy efficiency of this process for BrO3 ˉ removal was found to be enhanced by increasing sulfite dosage, as indicated by calculation of electrical energy per order (EE/O). Meanwhile, this process was proven to be economical for BrO3 ˉ removal. This study might provide a new outlook on the UV/sulfite process for real applications. Highlights: Effect of O2 on BrO3 ˉ reduction was mitigated by increasing sulfite dosage. Effect of humic acid on BrO3 ˉ reduction relied on its functional groups. Besides eaq ˉ, SO3 − also contributed to BrO3 ˉ reduction. Energy efficiency was enhanced by increasing sulfite dosage.